Testing concavity of a telescope mirror by processing of a single interferogram - Montalvo, R. A. (2015)
This paper shows that it is possible to estimate, from a single interferogram image, the error of the concave shape for an optically polished surface that will be used as a mirror in a reflecting telescope. In the Optics Laboratory of the PUCP, a Twyman-Green interferometer has been implemented; surface images with overlapping interference fringes known as interferograms are acquired. Algorithms based on Fourier transform allows the reconstruction of the surface shape and its deviation from ideal concave shape. Images were evaluated for different numbers of interference fringes in the same surface; in each case, a single image was necessary to determine surface error with the added advantage of not having contact with the surface.